PENILAIAN DAYA TARIK WISATA ALAM HUTAN KOTA GUNUNG SARI KOTA SINGKAWANG - Hermawan, Dimas; rizal, Fah; Dirhamsyah, M. (Universitas Tanjungpura, 2015)
Singkawang, a city located in the province of West Kalimantan has some attractive tourist spots and one of them is Urban forest of Mount Sari. Urban forest of Mount Sari is managed by city government of Singkawang and until now it has been developed maximal corresponding to aspects of tourism. Accordingly, research on the assessment of tourist spot in that area is very necessary as one of the important efforts to determine the planning in the field of natural tourist spot. Based on those considerations, the researcher wants to know more details about the attractiveness of the urban forest of Mount Sari especially with regard to aspects of tourism. This study aims to investigate the tourist spot of urban forest of Mount Sari. The method used in this research is descriptive method that is based on the standart Raw Research Development and Utilization of Natural Tourist spot 1983/1984. The result indicated that the urban forest of Mount Sari got a total score of 799.14 and it is categorized FAIR (C) to be developed into a natural tourist spot. Keywords: Mount Sari, Singkawang City, Urban Forest